2015
DOI: 10.1007/s10640-014-9868-7
|View full text |Cite
|
Sign up to set email alerts
|

The Opportunity Costs of Conservation with Deterministic and Probabilistic Degradation Externalities

Abstract: This experimental study examines variations in the opportunity cost of conservation in two linear appropriation games that include symmetric and asymmetric subject payoffs. In the first game, appropriation leads to deterministic degradation in the value of a shared resource. In the second game, appropriation leads to both deterministic and probabilistic degradation, introducing endogenous uncertainty in the value of the opportunity cost of conserving the shared resource. The results show that subjects systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Concurrently, decision sheets were distributed to subjects, who then completed two copies using pen and paper: one to hand back to the experimenter after all decisions were final and one to keep until the end of the session. As in Brandts and Schram (2001), Goeree et al (2002), and Blanco, et al (2015), it was the subjects' choice to determine the order in which he/she made decisions in the seven decision situations. Importantly, the decision for any situation could be revised as long as the experimenter had not announced that the time to make decisions had ended.…”
Section: The Experimental Decision Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, decision sheets were distributed to subjects, who then completed two copies using pen and paper: one to hand back to the experimenter after all decisions were final and one to keep until the end of the session. As in Brandts and Schram (2001), Goeree et al (2002), and Blanco, et al (2015), it was the subjects' choice to determine the order in which he/she made decisions in the seven decision situations. Importantly, the decision for any situation could be revised as long as the experimenter had not announced that the time to make decisions had ended.…”
Section: The Experimental Decision Settingsmentioning
confidence: 99%
“…For variation in the private return seeFischer et al (1995),Falkiner et al (2000),Palfrey and Prisbrey (1996),Brandts and Schram (2001), andBlanco et al (2015). For variation in the marginal value of the public good, seeIsaac and Walker (1988),Bagnoli and McKee (1991),Isaac et al (1994),Offerman et al (1996),Chan et al (1999),Tan (2008),Reuben and Riedl (2009),Carpenter et al (2009), andFischbacher et al (2015).…”
mentioning
confidence: 99%
“…It has been shown that making returns from aggregate group investments uncertain lowers individual contributions to the public good (Dickinson 1998;Gangadharan and Nemes 2009). Blanco et al (2015Blanco et al ( , 2016b use a different setting, where subjects are asked to withdraw funds from the group fund to the private account, instead of contributing to the public good. The authors show that introducing uncertainty over the size of the group fund or the probability of destruction of some funds therein increases appropriation from the group fund.…”
Section: Introductionmentioning
confidence: 99%
“…The formal approach presented is related to the theoretical and experimental literature on the effect of environmental uncertainty on the equilibrium outcomes in common-pool resource games (Budescu et al 1992, 1995, Biel and Garling 1995, Hine and Gifford 1996, Botelho et al 2014, Aflaki 2013Antoniadou et al 2013, Kimbrough and Wilson 2013, Safarzynska 2013, Schill et al 2015, Blanco et al 2016, 2017. In a standard harvesting set-up, individuals request resources from the common pool (e.g., Rapoport et al 1992).…”
Section: Introductionmentioning
confidence: 99%